FRI0563 It's More than Dryness and Fatigue: The Patient Perspective on Health-Related Quality of Life in Primary Sjögren Syndrome - A Qualitative Study. (15th July 2016) - Lackner, A.; Ficjan, A.; Unger, J.; Graninger, W.; Dejaco, C.
Abstract : Background: Patients with primary Sjögren Syndrome (PSS) are affected by glandular and extraglandular manifestations leading to physical and mental impairment. How these factors affect the health related quality of life (HRQL) of these patients is largely unexplored. Objectives: This qualitative study was conducted to investigate patients' perspectives and needs influencing HRQL in PSS. Methods: We recruited 20 consecutive PSS patients fulfilling the American-European consensus classification criteria out of the PSS cohort of the Medical University Graz, Austria. A total of 6 focus group sessions were performed. A discussion guide with four open-ended questions was developed containing all elementary components of HRQL (physical, mental, social, daily life). All interviews were audio-recorded and transcribed verbatim. A modified meaning condensation procedure was used to analyse the data. Results: All patients were female, the mean age was 61 (SD ±8) years and mean disease duration was 5 (±2) years. The focus group sessions took on average 58 ±13 minutes. The number of patients in each group ranged from three to four. The interview analysis resulted in 484 meaning units, 254 subconcepts and 87 concepts. The identified concepts were grouped into three dimensions: physical dimension, psychological & emotional challenges and social life & daily living. An inter-dependency of the three dimensions was identified. The concepts most commonly reported belonged to the physical dimension: pain, dryness and complaints related to these two symptoms. Patients frequently mentioned consequences of dryness including recurrent inflammation of eyes and ears, loss of sense of smell and taste, sleeping disturbances and the inability to eat and chew. In the dimension psychological & emotional challenges, the most frequently mentioned concepts were "being worried about the future", "a long symptom to diagnosis lag" and "the feeling of being an encumbrance for their families". Concepts like dependency on relatives in daily life, difficulties at work and financial burden were classified within the dimension of social life & daily living. Conclusions: We found that three interrelated dimensions (physical dimension, psychological & emotional challenges and social life & daily living) best reflected patients' experiences and feelings related to PSS. HRQL in PSS patients was influenced not only by dryness rather psychological and social burden clearly impacted the patients. Disclosure of Interest: None declared